Manic behaviour induced by deep-brain stimulation in Parkinson's disease: evidence of substantia nigra implication?. Issue 12 (16th November 2006) - Ulla, M; Thobois, S; Lemaire, J-J; Schmitt, A; Derost, P; Broussolle, E; Llorca, P-M; Durif, F
Abstract : We report the case of a patient who had benefited from bilateral subthalamic nucleus deep brain stimulation for Parkinson's disease and who presented acute and reproducible manic behaviour when stimulated mainly in the substantia nigra. A positron emission tomography scan showed an activation of the right dorsolateral prefrontal and inferior temporal cortex, the left anterior cingulate cortex and a deactivation of the left insula. This suggests that changes in cortical activation related to mania are subcortically driven, involving notably the substantia nigra.